Busana Keraton Surakarta Hadiningrat - Soedibyo, Mooryati, B.R.A., 1928-; Wibisono, Singgih; Soekarman, M. Sulebar, 1943-; Wasito, Wiyono Undung ([Jakarta] : PT Gramedia, 2003)
Traditional costumes of Surakarta Sultanate
References: p. (133)
Keywords: Costume -- Indonesia -- Surakarta; Clothing and dress -- Indonesia -- Surakarta